Evaluation of a Standardized Protocol for Plasma Rich in Growth Factors Obtention in Cats: A Prospective Study - Miguel-Pastor, Laura; Satué, Katy; Chicharro, Deborah; Torres-Torrillas, Marta; del Romero, Ayla; Peláez, Pau; Carrillo, José M.; Cuervo, Belén; Sopena, Joaquín J.; Cerón, José J.; Rubio, Mónica (Frontiers in Veterinary Science, 2022)
Objectives: The objectives of this study are: firstly to determine and compare the concentrations of platelets (PLT), red blood cells (RBC) and white blood cells (WBC) between whole blood (WB) samples, platelet rich plasma (PRP) and platelet poor plasma (PPP) samples; secondly to analyze the concentrations of platelet-derived growth factor BB (PDGF-BB) and transforming growth factor β1 (TGF-β1) in the PRP and PPP fractions of healthy adult cats using a standardized protocol with PRGF®-Endoret® characteristics. Materials and methods: A prospective study was conducted. WB was collected from 30 cats. PRP was obtained following three centrifugation protocols using PRGF®-Endoret® technology: 255 g, 260 g, and 265 g for 10 minutes each. The cellular components, RBC, WBC, PLT, and the concentrations of PDGF-BB and TGF-β1 in the PRP and PPP fractions were determined for each protocol. Results: PLTs in the PRP fraction was statistically higher than in WB, with no statistical differences between the PPP and WB fractions. PLT concentration in the PRP fraction obtained through the three protocols reached a mean value 1.5 times higher than baseline in 46.7%, 38 % and 43.3% of the analyzed samples respectively, without statistical differences among them. The mean platelet volume (MPV) was significantly higher in WB compared to PRP and PPP fractions without significant differences between protocols or between the different plasma fractions. Compared to WB, the number of RBCs and WBCs was reduced by 99% and by more than 95% in PRP and PPP, respectively, without significant differences between protocols. PDGF-BB concentrations were statistically higher in PRP than in PPP fractions, however, TGF-ß1 concentrations did not vary between fractions. No differences in PDGF-BB and TGF-ß1 concentration were observed between protocols. Clinical relevance: This study shows new scientific evidence regarding the obtention of PRP in cats using the PRGF®-Endoret® technology for the quantification of PDGF-BB and TGF-ß1 GFs. The protocol at 265 g 10 min increased PLT concentration by 1.5 times without erythrocytes and leukocytes. These results clearly show that the PRGF®-Endoret® methodology is suitable for obtaining PRP in cats. Future studies are needed to determine clinical efficacy of the obtained PGRF in cats.